PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK DENGAN MEDIA VIDEO DALAM PEMBELAJARAN MENULIS TEKS NEGOSIASI. - Maskur Subaweh, Ahmad; Muthmainnah, Fithry; Suciyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The author's concern regarding students' writing skills, who face difficulties in writing negotiation texts, and the limitations of teachers in designing varied learning models, motivated this research. This study is entitled